PEMBENTUKAN KELOMPOK REMAJA PENGELOLA SAMPAH DESA TANJUNG LUAR, KERUAK, LOMBOK TIMUR - Al Idrus, Agil; Ningsih, Baiq Hidayati; Surhayani, Evi; Maulidan, Fauzan; Febrianti, Ita Ayu; Pinandar, Lalu Sabde; Ali, Muh. Reza Isnan; Piazuri, Neza Luna; Saputri, Nurmala; Febrianti, Reni; Wahyudi, Sukron (Universitas Mataram, 2024)
Waste is still a big problem, especially plastic waste which is difficult to recycle because people still think with the old pattern that throwing it on beaches and rivers is enough to make the waste disappear. One of the things that must be done to overcome this problem is to manage waste. Waste management is a problem that has not been resolved properly. Tanjung Luar village is one of the densely populated villages, which causes a lot of waste to be produced. Therefore, in the PMD Community Service Program at the University of Mataram, a group of youth waste managers was formed to help Tanjung Luar Village in managing existing waste. This program is also assisted by several companion programs, such as making trash cans and transporting waste. The KKN Team hopes that by holding this activity, it will increase the community's understanding of the importance of increasing the knowledge and awareness of the Tanjung Luar Village community regarding the negative impacts and dangers of waste on health, increase the sense of environmental and health awareness regarding waste disposal behavior.